Impact of modified atmosphere packaging and ozonated water on the shelf life, quality, and safety of vegetables stored at non optimum temperatures - Stanley, Helena; Batziakas, Konstantinos G; Gragg, Sara E; Rivard, Cary L; Pliakoni, Eleni D (Journal of Postharvest Technology, 2020)
The objective of this paper was to investigate the effects of passive MAP at non-optimum storage temperature, with and without ozonated  washing, on the quality, safety, and shelf life of asparagus (Asparagus officinalis), broccoli (Brassica oleracea) and spinach (Spinacia oleracea).  Six treatments were examined: unwashed produce stored in produce bags and in MAP bags (washed in ice-cold water stored in produce bags  and in MAP bags; and washed in ozonated water stored in produce and in MAP bags. Samples were stored at 13oC at 95% RH. Product quality  was evaluated in terms of overall visual quality, color, and texture. Microbiological analyses included psychrotrophs, total aerobic  microorganisms, generic Escherichia coli, coliforms, and yeast and mold populations. The MAP bags equilibrated to an atmosphere of 3.5% CO2 and 8% O2 for asparagus, 12% CO2 and 3% O2 for broccoli, and 7% CO2 and 4-6% O2 for spinach. Asparagus, broccoli, and spinach stored in  MAP bags had a storage extension of 4, 7 and 7 days, respectively, compared to those in produce bags. The use of MAP prevented yellowing in  broccoli and spinach, and preserved visual texture and wilting in spinach. Ozonated water did not significantly affect the quality attributes in any  crop. No treatments had a significant effect on native microbial populations. These data indicate that the use of passive MAP bags for storing  broccoli and spinach under non-optimum temperatures could be an alternative for extending shelf life for growers without appropriate cold  storage access.
Keywords: Yellowing,; decay; aerobic plate counts; off-odor; broccoli,; spinach; asparagus